Analysis Of Criminal Decisions In The Pinangki Sirna Malasari Corruption Case In Terms Of The Principle Of Justice - Teddy Prayoga (JATIJAJAR LAW REVIEW, 2022)
In imposing a criminal decision, the judge must really understand whether the decision handed down has reached the target for the purpose of sentencing. The judge's decision is the culmination of a case that is decided and tried by the judge. The criminal system according to positive law, judges have the freedom to determine the severity of the crime to be imposed on the defendant between the general minimum to the special maximum. In 2020, Supreme Court Regulation Number 1 of 2020 concerning Guidelines for Criminalization Articles 2 and 3 of the Law on the Eradication of Corruption Crimes was established, which regulates the range of sentencing based on clarification of punishment covering state losses, aspects of error, aspects of impact, and aspects of the defendant's guilt. Therefore, judges as the spearhead of justice need to accommodate these fundamental values.The purpose of this paper is to examine the decisions of the Jakarta District Court Number 38/Pid.Sus-TPK/2020/PN Jkt.Pst and the Jakarta High Court Number 10/PID.TPK/2021/PT DKI in the decision-making process whether they are in accordance with the principles of justice in decision making. The writing method used in this study uses a normative juridical approach, the primary data needed are the Criminal Code, the Criminal Procedure Code, Law Number 31 of 1999 which has been amended by Law Number 20 of 1999. 2001 concerning Eradication of Criminal Acts of Corruption, Supreme Court Regulation Number 1 of 2020 concerning Guidelines for Criminalizing Article 2 and Article 3 of the Law on the Eradication of Criminal Acts of Corruption, Central Jakarta District Court Decision Number 38/PID.SUS-TPK/2020/PN JKT.PST , and the Decision of the Jakarta High Court Number 10/PID.SUS-TPK/2021/PT DKI, the secondary data needed are textbooks related to judges' considerations in sentencing, research results, works from legal circles, magazines, Newspapers, internet, and others related to the problem to be researched. The entire data was obtained by means of literature study and then analyzed using the theory of justice.Based on the results of this study, it shows that the basis for legal considerations by the judge in the decision of the Pinangki Prosecutor at the District Court is not in accordance with the theory of justice, while at the High Court it cannot be said to be correct. This can be seen in the judges' considerations that have not accommodated the values of certainty, justice and also the benefits of the law itself. Moreover, the High Court did not show the severity of the crime, instead it reduced the sentence. Whereas the suspect's status as a law enforcer or a prosecutor who should not violate a special obligation of office. Therefore, the judge in making his decision must be careful, avoiding as little as possible inaccuracies in every decision making.